Preparation And Characterization Of Chitosan-Enr50 Biocomposites And Their Potential Application As Slow-Release Biodegradable Matrices For Cu(Ii) And 2-Naphthol In Aqueous Media - Raju, Gunasunderi (2014)
Over the years incorporation of chitosan in the matrices of elastomers has been of interest to researchers. However, solubility of chitosan in acidic aqueous media in contrast with epoxidized natural rubber which is not soluble has been a limitation. This has prompted us to investigate and hereby report our findings on the preparation, characterization, and the properties of three types of biocomposites containing chitosan (CTS) and epoxidized natural rubber (ENR) prepared via different methods. The first type, CTS-g-ENR, was obtained via acid-induced reaction of ENR50 with CTS in the presence of AlCl3.6H2O. Moreover, the NMR spectral analysis revealed that the epoxy content of CTS-g-ENR-P1 is 22.36%, suggesting that the grafting of CTS onto the backbone of the ENR had occurred. This revelation is affirmed by the presence of the characteristic absorption bands of CTS and ENR and the appearance of new bands at 1219, 902, and 733 cm-1 in the infrared spectrum of CTS-g-ENR-P1. The Tg of CTS-g-ENR-P2 is determined to be 2.88 °C which is significantly higher than that of ENR50 (-27.2 °C). The thermal stability of CTS-g-ENR is found to be higher compared to that of CTS, but lower than the one for ENR50. SEM micrographs of CTS-g-ENR-P1 show a smooth topographical texture with no phased-out entity, confirming that CTS has been successfully grafted onto the backbone of the ENR.